Seroprevalence of Neospora caninum in goats (Capra hircus) from the Piura region, Peru - Aranda H., María (2023)
The aim of this study was to determine the seroprevalence of Neospora caninum in goats from eight provinces of the Piura region, Peru. In total, 361 sera were analysed with the commercial ID Screen Neospora caninum Competition ELISA kit for the detection of anti-N. caninum IgG antibodies. A general seroprevalence of 3.32% (95% CI 1.47-5.17) was found. The province of Morropón presented the highest frequency with 8.11% (95% CI 0-16.91) and the goats of Huancabamba, Paita, Sechura and Talara were seronegative. The animals seropositive to N. caninum were adults (>1 year) and were living at an altitude ≤500 meters above sea level.